How Much is Enough? An Evidence-Based Framework for Setting Medicaid Payment Rates - Kevin Quinn (SAGE Publishing, 2007)
This article proposes an evidence-based framework for Medicaid programs to use in setting payment levels for any health care service. The purpose of payment is seen from the beneficiary's perspective, that is, enabling access to quality services. The approach is to measure access as directly as possible, to make findings about payment adequacy, and to take action in a way that maximizes the return (i.e., access to quality care) on Medicaid's investment. This approach differs from both the theoretical ideal and from much of the past practice in Medicaid rate setting. The paper offers examples of evidence, findings, and actions.